(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
This article provides information on the impact of various environmental problems on economic security, environmental security and environmental threats, including green economy, principles of green economy, and solutions to environmental problems and countermeasures in the Republic of Uzbekistan. and offers are made.